Polydatin combined with hawthorn flavonoids alleviate high fat diet induced atherosclerosis by remodeling the gut microbiota and glycolipid metabolism - Li, Dan; Li, Yujuan; Yang, Shengjie; Zhang, Xiaonan; Cao, Yu; Zhao, Ran; Zhao, Yixi; Jin, Xiao; Lu, Jing; Wang, Xinyue; Wang, Qiutao; Liu, Longtao; et al. (Frontiers in Pharmacology, 2025)
BackgroundAtherosclerosis is a widely studied pathophysiological foundation of cardiovascular diseases. Inflammation and dyslipidemia are risk factors that promote the formation of atherosclerotic plaques. The gut microbiota and their metabolites are considered independent risk factors for atherosclerosis. Polydatin combined with hawthorn flavonoids, as the extracts of Polygonum cuspidatum Sieb. et Zucc. and Crataegus pinnatifida Bunge, have shown excellent cardiovascular protective effects. However, the underlying mechanism requires further investigation. Our study aimed to explore the anti-atherosclerotic mechanism through gut microbiota and their metabolites.MethodsApoE−/− mice were fed either a normal-chow diet or a high-fat diet. The polydatin combined with hawthorn flavonoids group received varied doses of polydatin and hawthorn flavonoids: a high dose (polydatin 200 mg/kg daily; hawthorn flavonoids 100 mg/kg daily), a medium dose (polydatin 100 mg/kg daily; hawthorn flavonoids 50 mg/kg daily), and a low dose (polydatin 50 mg/kg daily; hawthorn flavonoids 25 mg/kg daily). The control and model groups were administered distilled water (0.2 mL daily). The experiment lasted for 24 weeks.ResultsPolydatin combined with hawthorn flavonoids administration significantly reduced lipid and inflammatory cytokine levels, meanwhile, the atherosclerotic lesions in a high-fat diet-induced ApoE−/− mice were significantly decreased. Additionally, polydatin combined with hawthorn flavonoids also inhibited the enhancement of trimethylamine N-oxide (TMAO), trimethylamine (TMA) levels of HFD-induced ApoE−/− mice by regulating the expression of hepatic flavin-containing enzyme monooxygenase 3 (FMO3). 16S rRNA sequencing results demonstrated that high-dose polydatin combined with hawthorn flavonoids treatment increased the abundance of Actinobacteriota, Atopobiaceae and Coriobacteriaea_UCG-002, and decreased the abundance of Desulfobacterota. Norank_f_Muribaculaceae was enriched in the medium-dose polydatin combined with hawthorn flavonoids and simvastatin groups, and Lactobacillus was mainly increased in the simvastatin and the low-dose polydatin combined with hawthorn flavonoids groups. According to the metagenetic results, functional annotations also suggested that the biological processes of each group mainly focused on metabolism-related processes. Specifically, polydatin combined with hawthorn flavonoids may regulate the abundance of TMA-producing bacteria (Coriobacteriaceae, Desulfovibrio, Muribaculum, and Clostridium) and related enzymes in glycolipid metabolic pathways to exert an important effect on the prevention of atherosclerosis.ConclusionOur results suggested that polydatin combined with hawthorn flavonoids could regulate the glucolipid metabolism-related pathway, attenuate inflammatory cytokine levels, and reduce atherosclerotic plaques by remodeling gut microbiota.